Muscle‐specific Perilipin2 down‐regulation affects lipid metabolism and induces myofiber hypertrophy. Issue 1 (4th October 2018) - Conte, Maria; Armani, Andrea; Conte, Giuseppe; Serra, Andrea; Franceschi, Claudio; Mele, Marcello; Sandri, Marco; Salvioli, Stefano
Abstract: Background: Perilipin2 (Plin2) belongs to a family of five highly conserved proteins, known for their role in lipid storage. Recent data indicate that Plin2 has an important function in cell metabolism and is involved in several human pathologies, including liver steatosis and Type II diabetes. An association between Plin2 and lower muscle mass and strength has been found in elderly and inactive people, but its function in skeletal muscle is still unclear. Here, we addressed the role of Plin2 in adult muscle by gain and loss of function experiments. Methods: By mean of in vivo Plin2 down‐regulation (shPlin2) and overexpression (overPlin2) in murine tibialis anterior muscle, we analysed the effects of Plin2 genetic manipulations on myofiber size and lipid composition. An analysis of skeletal muscle lipid composition was also performed in vastus lateralis samples from young and old patients undergoing hip surgery. Results: We found that Plin2 down‐regulation was sufficient to induce a 30% increase of myofiber cross‐sectional area, independently of mTOR pathway. Alterations of lipid content and modulation of genes involved in lipid synthesis occurred in hypertrophic muscles. In particular, we showed a decrease of triglycerides, ceramides, and phosphatidylcoline:phosphatidylethanolamine ratio, a condition known to impact negatively on muscle function. Plin2 overexpression did not change fibre size; however, lipid composition was strongly affected in a way that is similar to that observed in human samples from old patients. Conclusions: Altogether these data indicate that Plin2 is a critical mediator for the control of muscle mass, likely, but maybe not exclusively, through its critical role in the regulation of intracellular lipid content and composition.